Secuencia didáctica en educación remota basada en metodología Steam y enfocada en los Ods con estudiantes del grado undécimo del Colegio Americano de Bucaramanga (2021)
The objective of this article is to evaluate the effect obtained after applying a didactic sequence based on the STEAM model and focused on Sustainable Development Goals (SDGs). Evaluation is done by applying the test of attitudes towards environmental issues of Fuentealba and Soto (2016) before and after the application of the sequence, considering only the items that relate to the environmental problems "water", "energy", "natural spaces", "recycling" and "transport". The test is applied to an experimental group and a control group, each group made up of 25 eleventh-grade students. The results show that the sequence had an impact on the experimental group. Quantitatively, it is evaluated with the Student’s T-test for related samples, comparing the results obtained by the experimental group before and after the application of the sequence. The test yields a p-value of 0.000, which indicates that there is a statistically significant difference between the test results with a confidence level of 95%. When the same comparison was made for the control group, a p-value of 0.291 with 95% confidence was obtained, which implies that there is no significant difference between the results obtained by this group. Qualitatively, the comments of some students show interest in particular environmental issues, fascination with relevant news, curiosity when asking questions that they found relevant, and an attitude and willingness to carry out the activities of the didactic sequence.